Inter and Intra Variation of Potato Yellow Vein Virus in Three Potato Species From Colombia (2015)
Abstract. Potato yellow vein virus (PYVV), (family Closteroviridae, genus Crinivirus) is a re-emergent virus in Andean countries. Low inter-isolate variation has been reported for PYVV CP gene, but there are no reports for intra-isolate variation. Inter- and intra-isolate variability in CP from a population of PYVV was studied. Samples of 216 symptomatic potato plants (115 Solanum tuberosum subsp. andigena (STA), 100 Solanum phureja (SPH) and 1 Solanum chaucha (SCH)) were collected in five Colombian departments. Viral isolates were amplified by RT-PCR and the amplicons were analyzed by single-strand conformation polymorphism (SSCP). Six different migration SSCP patterns (A to F) with different complexities were observed among the population. Pattern A was detected in the five departments in 66% of the isolates. Pattern E was found only in the department of Cundinamarca with a frequency of 0.09%. Patterns B, C, D and F were found in similar proportions of from 13% to 5.6% and were present in the five departments. Homology at the nucleotide level of 75% of the sequence of the CP gene was greater than 99% and the dN/dS ratio (no-synonymous/ synonymous changes) was 0.002. Amplicons of the whole CP gene of eight selected isolates representing the six SSCP patterns were cloned and the SSCP analysis showed that, in all cases, more than one variant was present. The sequence analysis of the 35 clones confirmed intra-isolate variability of PYVV. The existence of several variants in a single field isolate was demonstrated and negative selection against amino acid changes of the CP was suggested.  /  Resumen. Potato yellow vein virus (PYVV), (familia Closteroviridae, género Crinivirus) es un virus re-emergente para los países Andinos. Se ha reportado baja variación del gen CP de PYVV entre aislados, pero no hay reportes de variación intra aislado. Se estudió tanto la variación inter como intra aislado del CP de una población de PYVV. Muestras de 216 plantas de papa sintomáticas (115 Solanum tuberosum subsp. andigena (STA), 100 Solanum phureja (SPH) y 1 Solanum chaucha (SCH)) se colectaron en 5 departamentos de Colombia. Los aislados se amplificaron por RT-PCR y los amplicones se analizaron por polimorfismo conformacional de cadena sencilla (SSCP). Se observaron seis patrones de migración de SSCP distintos (A a F) con diferentes complejidades. El patrón A fue detectado en cinco departamentos en 66% de los aislados y el E solo en el departamento de Cundinamarca con una frecuencia de 0,09%. Los patrones B, C, D y F se encontraron en proporciones similares entre 13% a 5,6%, y estuvieron presentes en los cinco departamentos. La homología de nucleótidos del 75% de la secuencia del gen CP fue mayor del 99% y la tasa dN/dS (cambios no sinónimos/ cambios sinónimos) fue de 0,002. Amplicones del gen completo de CP de ocho aislados que representaban los seis patrones de SSCP se clonaron y un análisis SSCP mostró que todos tenían más de una variante. El análisis de secuencias de 35 clones confirmó la variabilidad intra aislado de PYVV. La existencia de varias variantes en un solo aislado de campo se demostró y se sugiere selección negativa de cambios de aminoácidos en al CP.